Diseño de un sistema de costos abc para la línea de lácteos del centro experimental y de producción salache de la Universidad Técnica De Cotopaxi - Aimacaña Casa, Verónica Alexandra (2019)
The main objetive of our integrating project was based on the design of an ABC costs systems for the dairy line of the Experimental Center and Production Salache, with the purpose of determining the correct costs that are inmerse in the activities of the academic process, previously CEYPSA (Experimental Center and Production Salache used an empirical costs systems, where the three elements of the costs are not taken into account, more than just the raw material. The methodology applied was based on the recognition of the object of the costs in this case the products; then an interview was held in the order collect information that allowed us to recognize the activities that are carried out in the academic process, in addition through the observation form, the resources used in the elaboration of yogurt were recognized, determining that CEYPSA calculates in an erroneous way the selling Price of the product. With the design of the system, it has been possible to establish each of the elements with accuracy getting the real cost, the time and the people that participate in the activities of execution of the word of elaboration of the beaten yogurt, contributing in this way to obtain a more acceptable utility, the same thing that can be reinvested in the improvement of academic processes. The management of the system helped to measure the performance of the activities, using resources in a better way, allowing in this way to generate added value to the product, through the cost base on activities, it was demostrated that the price established by Experimental Center and Production Salache, is smaller compared to the proposal, because the agroindustry plant only takes into account the raw material, leaving aside labor and indirect manufacturing costs, preventing knowing the reality of production.